The SAGES Manual Transitioning to Practice - Renton, David B.; Nau, Peter; Gee, Denise W. (Springer International Publishing : Imprint: Springer, 2017)
This SAGES manual will help educate and advise our new and recent surgical graduates on entering the job market. From how to find a job, to contract negotiations, to research and grant proposals, this manual offers pertinent strategies crucial to both surgical and non-surgical subspecialty fields. Chapters focusing on work-life balance and finding a mentor offer helpful insight to prevent burnout and optimize one's new career. The SAGES Manual: Transitioning to Practice will fill the gap in resident education and prove a useful text for residents, fellows and recent graduates as well as practicing surgeons in all subspecialties of surgery.
Keywords: Medicine.; Surgery.; elektronické knihy; electronic books